PEMBELAJARAN PEMAHAMAN MEMBACA PUISI PADA SISWA KELAS IV SD MELALUI MODEL KOOPERATIF TIFE THINK PAIR SHARE (TPS) - Indriyani, Tri Sila; Kelana, Jajang Bayu (COLLASE (Creative of Learning Students Elementary Education), 2021)
This research is motivated by the low level of students understanding the concept of the material well. This study aims to obtain a description of the achievement and improvement of poetry reading comprehension skills for fourth-grade elementary school students using the Think Pair Share (TPS) model. The research method used in this research is a qualitative descriptive method. In this study, the population was taken as grade IV SD students. As for the samples of this study were students of the Mutiara Bunda Elementary School in Bandung City class 4 Surfing, totaling 20 people. The instrument used in this study was a short questionnaire containing 5 questions of poetry text. Data analysis was carried out by qualitative descriptive. The data is taken from the results of observations, interviews, written tests, and filling out questionnaires. In the calculation of test instruments and data processing using Microsoft Excel and SPSS 22 programs. Based on the results of the research, it was found that the students' reading comprehension ability to read poetry was achieved using the Think Pair Share model. Students find it easier to understand the meaning and vocabulary in poetry as well as train their confidence by expressing opinions and discussing with their partners in small groups.